2003
DOI: 10.1021/es0263083
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Deposition of V, Cr, and Ni since the Late Glacial:  Effects of Climatic Cycles, Human Impacts, and Comparison with Crustal Abundances

Abstract: Vanadium, Cr, and Ni accumulating in a Swiss peat bog since 12 370 14C yr B.P. have been measured using inductively coupled plasma-mass spectrometry (ICP-MS) after acid dissolution in a microwave autoclave. Strict quality control schemes were applied to guarantee the accuracy of the applied analytical methodology. The concentration gradients in the peat column and comparison with Pb indicate that V, Cr, and Ni are effectively immobile in the ombrotrophic section of the peat profile but that Ni is added to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 39 publications
2
51
0
1
Order By: Relevance
“…In a peat core taken at a low-background area in Finland, post-depositional processes could not be excluded [132]. In contrast, the deposition of dust-related Ni phases appeared to be well preserved in an age-dated Swiss peat core (Figure 3) [129]. The highest concentrations of Ni were found during the Younger Dryas cold climate event (centered at 10 590 yr B.P.…”
Section: Peat Bogmentioning
confidence: 97%
See 2 more Smart Citations
“…In a peat core taken at a low-background area in Finland, post-depositional processes could not be excluded [132]. In contrast, the deposition of dust-related Ni phases appeared to be well preserved in an age-dated Swiss peat core (Figure 3) [129]. The highest concentrations of Ni were found during the Younger Dryas cold climate event (centered at 10 590 yr B.P.…”
Section: Peat Bogmentioning
confidence: 97%
“…In contrast, there are only a few systematic studies on the distribution and fate of Ni in ombrotrophic bogs [129][130][131][132][133][134]. The results indicate that the fate of Ni is strongly dependent upon the mineralogical form in which it is originally deposited, but also on the geochemical and hydrological conditions in the peat layers, and the peat accumulation rate [133].…”
Section: Peat Bogmentioning
confidence: 99%
See 1 more Smart Citation
“…Krachler et al (2003) concluded that Ni is mainly immobile in ombrotrophic peat, although it may be affected by weathering in minerotrophic peat. In contrast, Nieminen et al (2002) showed that Ni is mobile in ombrotrophic peat.…”
Section: Mobility Of Heavy Metals In Peat -A Short Reviewmentioning
confidence: 99%
“…Most importantly, peat is particularly effective at preserving atmospheric metal deposition in the form of lead (e.g. Shotyk, 2002;Shotyk et al, 1998Shotyk et al, , 2003Vile et al, 1999;Weiss et al, 1999), copper (Rausch et al, 2005;Mighall et al, 2002), nickel (Krachler et al, 2003) and zinc (Rausch et al, 2005;Twardowska et al, 1999). Recent research has shown that ancient Pb contamination in peat can be traced by Pb isotopes and fingerprinted to a local or regional origin (e.g.…”
Section: Introductionmentioning
confidence: 99%